The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1101/2022.05.16.492013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanding EMC Foldopathies: Topogenesis Deficits Alter the Neural Crest

Abstract: The endoplasmic reticulum membrane protein complex (EMC) is essential for the insertion of a wide variety of transmembrane proteins into the plasma membrane across cell types. Each EMC is composed of Emc1-7, Emc10, and either Emc8 or Emc9. Recent human genetics studies have implicated variants in EMC genes as the basis for a group of human congenital diseases. The patient phenotypes are varied but appear to affect a subset of tissues more prominently than others. Namely, craniofacial development seems to be co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Crucially, EMC1 performs the same function in the β‐catenin‐signaling pathway as EMC9 and 10. Deletion of EMC9 or EMC10 has been shown to result in NCC dysfunction by disrupting WNT signaling, leading to human disease 75 . Our research group has demonstrated an association between the deletion of EMC proteins and retinal degeneration, including EMC1, 3, and 6.…”
Section: An Overview Of Emc's Associated Diseases and Clinical Implic...mentioning
confidence: 80%
See 1 more Smart Citation
“…Crucially, EMC1 performs the same function in the β‐catenin‐signaling pathway as EMC9 and 10. Deletion of EMC9 or EMC10 has been shown to result in NCC dysfunction by disrupting WNT signaling, leading to human disease 75 . Our research group has demonstrated an association between the deletion of EMC proteins and retinal degeneration, including EMC1, 3, and 6.…”
Section: An Overview Of Emc's Associated Diseases and Clinical Implic...mentioning
confidence: 80%
“…Deletion of EMC9 or EMC10 has been shown to result in NCC dysfunction by disrupting WNT signaling, leading to human disease. 75 Our research group has demonstrated an association between the deletion of EMC proteins and retinal degeneration, including EMC1, 3, and 6. Specifically, we found that Emc1-specific knockout (KO) in mouse retina reduces levels of membrane proteins and ER chaperones, suggesting that the loss of membrane proteins is a primary cause of photoreceptor degeneration.…”
Section: Neurodevelopmental Disorder and Retinopathymentioning
confidence: 94%